2021
DOI: 10.1111/1745-9125.12287
|View full text |Cite
|
Sign up to set email alerts
|

The ties that bribe: Corruption's embeddedness in Chicago organized crime*

Abstract: tos, and Criminology editors and reviewers for comments on earlier versions of this work. We thank Duncan Temple Lang and John Daniels for computational support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…This facade of patriotism has not only allowed these far‐right groups to appeal to a greater swath of American society, but the meta‐politics 3 and rhetoric of the alt‐right has become so common by the GOP and mainstream conservatives, that the term alt‐right is hollowed out with little distinction today between them and conventional Republicans (e.g., “The Big Lie”) (see Blazak, 2022; Jacobson, 2021; Kyler & Charron‐Chénier, 2022; Lemire, 2002; Reyna et al., 2022; Selvanathan & Leidner, 2022; Thompson & Hawley, 2021). This public relationship between noteworthy members of a political party and a street gang, while not unheard of at the local level is a unique characteristic of Proud Boys, has existed historically but only tacitly between politicians and street gangs (see Hagedorn, 2006, 2008, 2015; Joseph & Smith, 2021; Smith, 2019).…”
Section: What Are Alt‐right Gangs?mentioning
confidence: 99%
“…This facade of patriotism has not only allowed these far‐right groups to appeal to a greater swath of American society, but the meta‐politics 3 and rhetoric of the alt‐right has become so common by the GOP and mainstream conservatives, that the term alt‐right is hollowed out with little distinction today between them and conventional Republicans (e.g., “The Big Lie”) (see Blazak, 2022; Jacobson, 2021; Kyler & Charron‐Chénier, 2022; Lemire, 2002; Reyna et al., 2022; Selvanathan & Leidner, 2022; Thompson & Hawley, 2021). This public relationship between noteworthy members of a political party and a street gang, while not unheard of at the local level is a unique characteristic of Proud Boys, has existed historically but only tacitly between politicians and street gangs (see Hagedorn, 2006, 2008, 2015; Joseph & Smith, 2021; Smith, 2019).…”
Section: What Are Alt‐right Gangs?mentioning
confidence: 99%
“…This is in part because criminals do their best to remain undetected, but also, and in fact primarily so, because this information is often classified and restricted to law enforcement agencies. Despite these difficulties, many recent works have demonstrated the usefulness of network science to investigate criminal networks, with examples including cartel detection 12 , corruption risk in contracting markets 13 , money laundering 14 , identification of corrupt politicians via voting networks 15 , dark web pedophile rings 16 , criminal conspiracy networks of companies 17 , modular structure of crime organizations 18 , political corruption networks 19 , organized crime networks 20 , controllability of criminal networks 21 , resilience of drug trafficking 22 , as well as police criminal intelligence networks 23 . Nevertheless, and despite the fascinating research that has already been made, we still need to identify overarching common properties and dynamical aspects of criminal networks, which might allow us to develop simple models that describe fundamental features and provide valuable insights into organized crime.…”
Section: Introductionmentioning
confidence: 99%
“…In line with other research on social systems [7][8][9][10][11] , complex networks can suitably describe the intricate relations among criminals and reveal the patterns based on which criminal organizations operate. Beyond theoretical explorations, recent articles have empirically demonstrated that these methods can be useful in investigations involving drug trafficking 12 , political networks 13,14 , police intelligence networks 15 , cartel detection 16 , money laundering 17 , pedophile rings 18 , and a range of other examples [19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%